Chatbots in Education: A Bibliometric Analysis of Publications from 2013-2023 - Widiyanto , Yovi; Abdul Muiz Lidinillah, Didin; Nuryadin, Asep (ATTA`DIB, 2025)
This study aims to analyze the development trend of researching articles related to chatbots in education. The method used in this study was bibliometric analysis with the help of the VOSViewer application. Publication data was collected using the Publish or Perish application to obtain article data in Google Scholar-indexed journals. This study analyzed publications from 2013 to 2023. An initial search found a total of 606 articles. The data was then processed and double-checked using the Microsoft Excel application. After double-checking, several articles were found that were the same, so the total number of articles collected was 598. The research development trend has increased yearly related to chatbots in education, except in 2023 because this research was conducted in june 2023. Topics often discussed recently besides the keywords used in searches were covid, higher education, natural language process, context, English performance, text, online learning, AI chatbot, and language learning. Most often used keywords were chatbot, analysis, learning, student, application, study, deep learning, system, machine learning, and machine. However, some topics should be discussed more, such as fields (fields of study in subjects) and analysis (analysis). It is expected that this study can be a starting point for other researchers to develop research on these topics.